'Like Adam and Eve': Biblical Models and Jewish Daily Life in Medieval Christian Europe. (February 2018) - Baumgarten, Elisheva
This article follows the exegetical and legal interpretations of the story of Adam and Eve among Jewish scholars of the High Middle Ages living in northern Europe. It argues that by following these evolving interpretations and understandings one can tease out details of the fabric of everyday Jewish life alongside tensions and norms that were under debate. It focuses on two main aspects of these reinterpretations. The first is understandings concerning conjugal life and gender hierarchies. The second is legal rights and responsibilities accorded to women as 'daughters of Eve.'